Addressing the regulatory and scientific challenges in multiple sclerosis – a statement from the EU regulators. (September 2014) - Balabanov, Pavel; Haas, Manuel; Elferink, Andre; Bakchine, Serge; Broich, Karl
Improving and facilitating the process of making new drugs available to patients with multiple sclerosis (MS) requires cooperation among the regulators and other stakeholders. This cooperation will also positively contribute towards developing guidelines of the highest quality in medical, regulatory and scientific aspects. This would be beneficial both in areas that require further guideline development, but also in fields where existing guidance should be adapted to take into account evolution in science. Considering the input from all stakeholders, the European Medicines Agency confirmed its intention to update the relevant guideline and apply a flexible approach towards new drug development strategies in MS. This article is the first official position from the EU regulators, presenting the main changes to be expected in the guidance document.